Evaluasi Penggunaan Obat Antimalaria di Rumah Sakit Umum Daerah (RSUD) Abepura, Jayapura - Deshinta S. Natalia; Elsye Gunawan; Rani D. Pratiwi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
Evaluation of drug use is a quality assurance process that is carried out continuously, organizational structured and recognized to ensure that the drug is used appropriately and effectively. Until recently, Jayapura city is still as a malarial endemic area. In 2012, the number of malaria cases are malarial tertiana 8.535 (39%) cases, malarial tropical 12.256 (57%), malarial mix (tertiana+tropical) 612 (2,84%) and malarial quartana 73 (0,33%). The highest percentage of malarial cases in the Jayapura city is caused by Plasmodium falciparum. The aims of this study are to evaluate the drug use and the dose accuracy of antimalarial drugs in the General Hospital of Abepura from July to December 2014. This is a descriptive study conducted by a retrospective review of medical records of patients. The results of the study concluded that the highest incidence rates occurred in the male (59.04%) and lowest in women (40.96%), 15-25 years of age (57.8%), 26-35 years of age (27.7%) and 36-45 years of age (14.5%). The dose accuracy for antimalarial drugs (100%) indicated that antimalarial drugs used are Primaquine, Artesunate injection and Dihydroartemisin + piperaquine (DHP) or Darplex. Key words: Abepura hospital, antimalarial drug, Jayapura, malaria